GENETIC DIVERSITY AMONG Colletotrichum sublineolum PATHOTYPES ISOLATED FROM SORGHUM (Sorghum bicolor) - FIGUEIREDO, JOSÉ EDSON FONTES; DEPAOLI, HENRIQUE CESTARI; COELHO, VINÍCIO TADEU DA SILVA; CASELA, CARLOS ROBERTO; FERREIRA, ALEXANDRE DA SILVA; GUIMARÃES, CLÁUDIA TEIXEIRA; GOMES, ELIANE APARECIDA; BRESSAN, WELLINGTON (REVISTA BRASILEIRA DE MILHO E SORGO, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:3.0cm 3.0cm 73.7pt 3.0cm; mso-header-margin:2.0cm; mso-footer-margin:36.0pt; mso-gutter-margin:5.65pt; mso-paper-source:15 0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif]–> Sorghum anthracnose, caused by Colletotrichum sublineolum is a serious disease in Brazil. The fungus is highly variable pathogenically with many physiological races. The present study was made to evaluate the usefulness of molecular methods (SDS-PAGE, RAPD, ARDRA and rDNA sequencing) for identifying C. sublineolum pathotypes isolated from sorghum. Although protein profile (SDS-PAGE) showed a relative low level of polymorphism, differences could be observed due to presence/absence of some polypeptides as well as to intensity of some bands among pathotypes. DNA profile of arbitrarily amplified sequences (RAPD) using sixteen random primers revealed a high degree of polymorphism while amplified rDNA (ITS region and 18S gene) digested with six different restriction enzymes (ARDRA) showed similar patterns. Nucleotide sequencing analysis of the complete ITS region and partial sequencing of 18S rRNA gene were useful for revealing genetic differences among the five pathotypes. In the present study, RAPD and rDNA sequencing were the most profitable methods for identifying C. sublineolum pathotypes.